2017
DOI: 10.1186/s13063-017-2126-x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, multi-center, prospective study comparing best medical treatment versus best medical treatment plus renal artery stenting in patients with hemodynamically relevant atherosclerotic renal artery stenosis (RADAR) – one-year results of a pre-maturely terminated study

Abstract: BackgroundThe indications for conservative “best medical treatment” (BMT) versus additional renal artery stenting are a matter of ongoing debate. The RADAR study aimed to evaluate the impact of percutaneous renal artery stenting on the impaired renal function in patients with hemodynamically significant atherosclerotic renal artery stenosis (RAS).MethodsRADAR is an international, prospective, randomized (1:1) controlled study comparing BMT alone versus BMT plus renal artery stenting in patients with duplex son… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 20 publications
0
17
0
4
Order By: Relevance
“…[13][14][15][16][17][18][19][20] Among the 8 available RCTs, the CORAL study (Cardiovascular Outcomes in Renal Atherosclerotic Lesions) confirmed the advantage of PTA plus medical therapy over medical therapy alone in terms of improving BP control, while these findings were confirmed only by 2 of the numerous nonrandomized studies. [13][14][15][16][17][18][19][20][21][22] Importantly, BP control with medical therapy does not prevent progression of RAS. Between 36% and 71% of patients were reported to experience progression during 5 years, 23 while renal artery occlusion within 1 year was observed in 16% of medically treated patients.…”
Section: Methodsmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20] Among the 8 available RCTs, the CORAL study (Cardiovascular Outcomes in Renal Atherosclerotic Lesions) confirmed the advantage of PTA plus medical therapy over medical therapy alone in terms of improving BP control, while these findings were confirmed only by 2 of the numerous nonrandomized studies. [13][14][15][16][17][18][19][20][21][22] Importantly, BP control with medical therapy does not prevent progression of RAS. Between 36% and 71% of patients were reported to experience progression during 5 years, 23 while renal artery occlusion within 1 year was observed in 16% of medically treated patients.…”
Section: Methodsmentioning
confidence: 99%
“…Some other studies 27,45 were unable to detect a clinically significant benefit from PTRA on left ventricular mass in patients with ARAS of 50% to 80%. When stenosis was ≥80% in a recently published RCT, 29 there was improvement in clinical outcomes in cardiac events in 3 years after PTRA. Iwashima et al.…”
Section: Discussionmentioning
confidence: 90%
“…One record was identified in a search of references. A total of 9 RCTs (EMMA, 23 SNRASCG, 24 DRASTIC, 25 STAR, 26 RASCAD, 27 CORAL, 28 RADAR, 29 NITER, 30 and ASTRAL 31 ) involving 2309 patients were chosen. Figure 1 shows a flowchart illustrating the search strategy for RCTs on PTRA and BMT in patients with ARAS.…”
Section: Resultsmentioning
confidence: 99%
“…3 The average eGFR of the population was under 60 mL/min in three other clinical studies. 4,14,15 Although RAS leads to renal dysfunction, the exact level of reduced renal perfusion can lead to hemodynamic changes. Visual assessment is widely used in diagnosing vascular diseases, but it is not accurate alone in evaluating the stenotic degree of lesions.…”
Section: Discussionmentioning
confidence: 99%
“… 3 The average eGFR of the population was under 60 mL/min in three other clinical studies. 4 , 14 , 15 …”
Section: Discussionmentioning
confidence: 99%